1995
DOI: 10.1002/j.1460-2075.1995.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the chromo domain of HP1.

Abstract: Heterochromatin protein 1 (HP1) is a non‐histone chromosomal protein in Drosophila with dosage‐dependent effects on heterochromatin‐mediated gene silencing. An evolutionarily conserved amino acid sequence in the N‐terminal half of HP1 (the ‘chromo domain’) shares > 60% sequence identity with a motif found in the Polycomb protein, a silencer of homeotic genes. We report here that point mutations in the HP1 chromo domain abolish the ability of HP1 to promote gene silencing. We show that the HP1 chromo domain, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
229
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(246 citation statements)
references
References 38 publications
15
229
1
1
Order By: Relevance
“…Previous studies have demonstrated that chromo domain-containing proteins, including Su(var)3-9 and its orthologs, localize to regions of chromatin that are transcriptionally silenced (1,22,39). Our own subnuclear localization of SUV39H1 to electron-dense nuclear foci supports the notion that SUV39H1 may associate with transcriptionally inactive chromatin.…”
Section: Sbf1 Physically Associates With the Set Domain Of Suv39h1supporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies have demonstrated that chromo domain-containing proteins, including Su(var)3-9 and its orthologs, localize to regions of chromatin that are transcriptionally silenced (1,22,39). Our own subnuclear localization of SUV39H1 to electron-dense nuclear foci supports the notion that SUV39H1 may associate with transcriptionally inactive chromatin.…”
Section: Sbf1 Physically Associates With the Set Domain Of Suv39h1supporting
confidence: 86%
“…The repressor property of SUV39H1 localized to its amino-terminal half which also contains a chromo domain, a modular motif that self-associates and assembles into multimeric complexes on chromatin (31,39,46). Notably, transcriptional repression by SUV39H1 did not require its SET domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This domain shares > 70% sequence identity with protein in Drosophila and mouse [26]. Recently it was shown that the HP1 chromo domain has chromosome binding activity and that proteins with this domain are recruited to their distinct chromosomal binding sites, probably due to protein-protein interaction [36]. It is generally acknowledged that autoepitopes on nuclear antigens are conserved and functional domain regions [5,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…DNA was counterstained with propidium iodide after RNase treatment. Immunostaining of polytene chromosomes from salivary glands was done using a 1:100 dilution of anti-ASF1 antibody (Platero et al 1995).…”
Section: Immunostaining Techniquesmentioning
confidence: 99%